The sounds of Milan, 1585-1650 - Kendrick, Robert L. (Oxford University Press, 2002)
In this book, a follow-up to his 1996 monograph Celestial Sirens, Robert Kendrick examines the cultural contexts of music in early-modern Milan. This book describes the churches and palaces that served as performance spaces in Milan, analyzes the power structures in the city, discusses the devotional rites of the Milanese, and explores the connections among city politics, city-scape, and music.